HUBUNGAN INTENSITAS KEBISINGAN DENGAN GANGGUAN PENDENGARAN PADA PEKERJA WOOD PREPARATION DI PT. LONTAR PAPYRUS PULP AND PAPER INDUSTRY TAHUN 2021 - Della Riska Hanum Chayandari; Putri Sahara Harahap; Idet Harianto (Jurnal Inovasi Penelitian, 2023)
Lontar Papyrus Pulp and Paper Industry in the WP (Wood Preparation) section (bark separator) there are many machines that make noise with noise intensity above the average TLV of 85 dB. The source of the resulting noise, namely from production machines, puts workers at risk of hearing loss. This research is an analytical study with a cross sectional approach. This research was conducted at PT. Lontar Papyrus Pulp and Paper Industry in the WP (Wood Preparation) section. The research sample is workers in the production section of PT. Lontar Papyrus Pulp and Paper Industry in the WP (Wood Preparation) section totaling 90 people. The sampling technique was the total sampling technique. Data were analyzed using the chi-square test and the Khrushall Wallis test. A total of 64.4% of respondents had no hearing loss, 24.4% of respondents had conductive hearing loss, 11.1% of respondents had sensory hearing loss. The average noise intensity is 91.23 dB, the average working period of the respondents is 20.68 years and as many as 72.5% of respondents have used Personal Protective Equipment according to SNI. The results of the bivariate analysis showed that there was a relationship between noise intensity (p = 0.003), years of service (p = 0.000) and the use of personal protective equipment (p = 0.016) with hearing loss among workers in the WP department at PT. Lontar Papyrus Pulp and Paper Industry. It is recommended that companies perform worker job rotation so that workers are not at risk of hearing loss